The Textology of the Synaxarian Life of Menas, Hermogenes, and Eugraphus, Martyrs of Alexandria - Čistiakova, Marina (Slavistica Vilnensis, 2021)
The abridged life of Menas, Hermogenes, and Eugraphus, martyrs of Alexandria, was translated from Greek as part of the Church Slavonic Synaxarion no later than in the early 12th century. Notably, the main version of this life does not contain any data on St Eugraphus. One of the earliest copies of the Synaxarion has lost the headline of the life of martyr Gemellus, whose memory is mentioned on the same day, while the corresponding text was added to the life of the saints of Alexandria. The scribe’s error has led to the emergence of a classifying feature that allows dividing the versions of the oldest translation of the Synaxarion into two groups. The first group consists of the main version of the life (Sof. 1324 and most other copies of the Ordinary Synaxarion). The second group encompasses the extended by the life of Gemellus edition (copies of the Bulgarian version of the Synaxarion and several copies of the abridged version). In the Serbian version of the Synaxarion the main version of the life was supplemented with fictitious data about martyr Eugraphus. Apart from the versions of the Ordinary Synaxarion, two independent translations of the Versed Synaxarion were made from Greek to Church Slavonic in the 14th century. One of them relates to the Bulgarian book tradition and the other one follows the Serbian one. Each of the two translations includes the new life of Alexandria’s martyrs supplemented with verses. Between the 1630s and 1640s, Ukrainian scribes of the Commonwealth of the Two Nations created yet another version of the life, where the main version was supplemented with data of martyr Eugraphus from the Bulgarian translation of the Versed Synaxarion. Thus, the abridged life of the martyrs of Alexandria is known in three translations, with the oldest one of them available in four versions.